2017
DOI: 10.29076/issn.2528-7737vol9iss21.2016pp49-57p
|View full text |Cite
|
Sign up to set email alerts
|

Aprendizaje Basado en la Investigación: caso UNEMII / Research-based learning: case UNEMI

Abstract: Este trabajo investigativo nace de la necesidad planteada en las diferentes normativas establecidas en Ecuador, en las que se evidencia la urgencia de transformar el sistema educativo nacional a través del desarrollo de la investigación en la educación superior, convirtiendo al uso del Aprendizaje Basado en la Investigación (ABI), en una buena estrategia didáctica para lograr su fin. Se pretende demostrar la relación existente entre el incremento de la producción científica docente y el uso de la metodología d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 1 publication
1
3
0
1
Order By: Relevance
“…The results obtained are similar to those found by Vergara (2022) Guadalupe et al, 2017). Likewise, the IBL shows substantial improvements in the evaluations that use rubrics, the results obtained by means of Friedman's non-parametric test indicate that the p-value (0.002) is lower than the established significance level (0.05) (Gamarra et al, 2022).…”
Section: Degree Of Relationship Between Inquiry-based Learning and Co...supporting
confidence: 86%
See 1 more Smart Citation
“…The results obtained are similar to those found by Vergara (2022) Guadalupe et al, 2017). Likewise, the IBL shows substantial improvements in the evaluations that use rubrics, the results obtained by means of Friedman's non-parametric test indicate that the p-value (0.002) is lower than the established significance level (0.05) (Gamarra et al, 2022).…”
Section: Degree Of Relationship Between Inquiry-based Learning and Co...supporting
confidence: 86%
“…These findings have similarity with Vergara (2022) who refers that according to Spearman's correlation coefficient (Rho) was 0.266**, indicating a low level positive correlation, in addition, the p=0.006 (<0.05) value establishes a relationship between the ability to process scientific information and research skills, which leads to the rejection of the null hypothesis. Also another study by Espinel-Guadalupe et al (2017) showed a significant increase in the use of scientific papers by students with 76.32%, as well as an increase in scientific production by teachers, inferring that there is a connection between students employing more scientific information in their independent work and teachers sharing their research in the classroom. Casa-Coila, M., D., Mamani-Vilca, P., S., Pari-Achata, D., Pacori-Zapana, E., Perez-Argollo, K., Paredes-Aliaga, J., S. (2024)…”
Section: Degree Of Relationship Between Information Processing and Co...mentioning
confidence: 97%
“…The results obtained indicate that research-based learning should be part of the curricular design of science subjects, especially physics, through research activities applying the scientific method that enable the development of scientific competences [29,30]. This requires a teacher who plans, so that he or she can guide the student in scientific research of a formative nature, which contributes to the formation of a critical, analytical, and autonomous student [22].…”
Section: Resultsmentioning
confidence: 98%
“…Although different precedents have had as their main objective the approach of methodologies like inquiry-based learning [22][23][24], however, this strategy is not widely applied by teachers in general, especially natural science teachers [25] learning have greater motivation and potential to do research, guided by the teacher [26]. Furthermore, the fact that knowledge of this method should be acquired from the first courses is highlighted.…”
Section: Resultsmentioning
confidence: 99%
“…Un amplio cuerpo de teorías existentes, proporcionadas por la pedagogía, la psicología de la educación y la didáctica, permiten establecer que la enseñanza basada en investigación es un modelo sólidamente fundamentado. Espinel et al (2016) destacan que pueden utilizarse varias estrategias: a) hablar a los estudiantes de los proyectos actuales de investigación, relacionados con los temas de la materia que se imparte en cada momento, b) incorporar los últimos trabajos de investigación realizados sobre un tema específico de la clase, c) contextualizar las discusiones de los resultados de investigación actuales, haciendo referencia a algunas de las teorías desacreditadas del pasado y los debates del presente y d) analizar la metodología y el argumento presentado en un artículo de revista que establezca hallazgos de investigaciones recientes. Todas estas estrategias se plantean en el presente proyecto.…”
Section: Introductionunclassified